2020
DOI: 10.5206/cjsotl-rcacea.2020.1.10804
|View full text |Cite
|
Sign up to set email alerts
|

World’s Greatest Challenges: Building Interdisciplinary Understanding and Collaboration among Business and Social Work Students

Abstract: Socially engaged students cross all disciplines. Today’s complex and rapidly changing environment poses new challenges for practitioners, students, and educators working within and alongside post-secondary institutions. This research explores how business and social work students interpret and perceive the world’s greatest challenges. Eighty-four students participated in the mixed methods study wherein a workshop was delivered to two social innovation and two social work classes. The workshops provided a forum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Milley et al (2020) found that of the social innovation initiatives in Canada, there was “minimal emphasis on innovation, disruption or change inside universities” (p. 31), suggesting that the current state of social innovation in Canadian post-secondaries focuses disruptive questioning outwards rather than inwards. While some cross-campus collaborations are promising (Pearl and Oliver, 2020), Benneworth et al (2020)’s hypothesize that the institutional logic of universities, while open to entrepreneurship, may actually provide a barrier between those organizations and social innovation - that there is a missing step between “enthusiastic managers and engaged professors” (31). This in turn undermines universities’ social engagement more broadly.…”
Section: Social Innovation In Post-secondary: Emerging Trends and Questionsmentioning
confidence: 99%
“…Milley et al (2020) found that of the social innovation initiatives in Canada, there was “minimal emphasis on innovation, disruption or change inside universities” (p. 31), suggesting that the current state of social innovation in Canadian post-secondaries focuses disruptive questioning outwards rather than inwards. While some cross-campus collaborations are promising (Pearl and Oliver, 2020), Benneworth et al (2020)’s hypothesize that the institutional logic of universities, while open to entrepreneurship, may actually provide a barrier between those organizations and social innovation - that there is a missing step between “enthusiastic managers and engaged professors” (31). This in turn undermines universities’ social engagement more broadly.…”
Section: Social Innovation In Post-secondary: Emerging Trends and Questionsmentioning
confidence: 99%